Plastic stress distribution in a rotating disk with rigid inclusion under a radial temperature gradient - Parmaksizoglu, C; Guven, U (MARCEL DEKKER INC, 1998)
This study investigates the plastic stress distribution in a rotating disk with rigid inclusion, under an axially symmetric steady-state temperature gradient. The analysis is based on Tresca's yield condition, its associated flow rule, and linear strain hardening material behavior.
Keywords: Mechanics